1-Bit Reconfigurable Unit Cell for Ka-Band Transmitarrays - Di Palma, Luca; Clemente, Antonio; Dussopt, Laurent; Sauleau, Ronan; Potier, Patrick; Pouliguen, Philippe (IEEE antennas and wireless propagation letters, 2016)
This letter presents an electronically reconfigurable, linearly polarized unit cell for transmitarray applications in Ka-band. A 1-bit phase resolution (namely with two phase states 0 ° and 180 °) is obtained using two p-i-n diodes mounted on a slot-loaded patch antenna. The design, realization, and experimental characterization in a standard waveguide simulator are reported. The measured insertion losses only reach 1.09 and 1.29 dB for the two-phase states, respectively, with a 3-dB transmission bandwidth of about 11.2%.